Why Does Therapy Work? An Idiographic Approach to Explore Mechanisms of Change Over the Course of Psychotherapy Using Digital Assessments - Altman, Allison Diamond; Shapiro, Lauren A.; Fisher, Aaron J. (Frontiers in Psychology, 2020)
Background and Objective(s): While psychotherapy treatments are largely effective, the processes and mechanisms underlying such positive changes remain somewhat unknown. Focusing on a single participant from a treatment outcome study that used a modular-based cognitive behavior therapy protocol, this paper aims to answer this question by identifying changes in specific symptomatology over the course of the treatment. Using quantitative data derived from digital health methodology, we analyzed whether a given therapeutic intervention was related to downstream effects in predicted symptom domains, to assess the accuracy of our interventions. Methods: This case study employed an observational N-of-1 study design. The participant (n=1) was a female in the age range of 25-35 years. Using digital health data from ambulatory assessment surveys completed prior to and during therapy, separate linear regression analyses were conducted to assess if hypothesized treatment targets reduced after a given module, or intervention. Results: Support was found for some of the hypothesized quantitative changes (e.g. decreases in avoidance after exposures module), yet not for others (e.g. decreases in rumination following the mindfulness module). Conclusions: We present data and results from our analyses to offer an example of a novel design that may allow for a greater understanding of the nature of symptom changes with increased granularity throughout the course of a psychological treatment from the use of digital health tools.